2011
DOI: 10.1111/j.1423-0410.2011.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Fresh frozen plasma quality: relation to age and gender of blood donors

Abstract: International Normalized Ratio, aPTT, FVIII, FV, fibrinogen and protein S, as quality indicators for the efficacy of therapeutic plasma, revealed a moderate correlation with age and gender. Compared with the usual reference ranges, the differences were not significant enough to identify any relevant imbalance between procoagulating, anticoagulating and fibrinolytic factors that might influence product quality where the increasing age of the donors or the preference of male donor plasma was concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
(61 reference statements)
5
6
1
Order By: Relevance
“…ADAMTS13 level is higher in females than in males in a Japanese population (Kokame et al, 2011), which is similar to our results. Consistent with our results, gender-related differences in FVIII (Favaloro et al, 2005; Kadir et al, 1999; Madla et al, 2012), Fbg (Madla et al, 2012), and VWF (Favaloro et al, 2005; Kadir et al, 1999) were not observed. However, Conlan et al (1993) reported that FVIII and VWF levels are significantly higher in females than in males.…”
Section: Discussionsupporting
confidence: 92%
“…ADAMTS13 level is higher in females than in males in a Japanese population (Kokame et al, 2011), which is similar to our results. Consistent with our results, gender-related differences in FVIII (Favaloro et al, 2005; Kadir et al, 1999; Madla et al, 2012), Fbg (Madla et al, 2012), and VWF (Favaloro et al, 2005; Kadir et al, 1999) were not observed. However, Conlan et al (1993) reported that FVIII and VWF levels are significantly higher in females than in males.…”
Section: Discussionsupporting
confidence: 92%
“…The influence of senescence of hematopoietic stem cells on the quality of donated blood was not in the focus of the study and deserves further studies. However, recently published data could not detect an influence of the age of donors on the quality of stored red blood cells [17] and no clinically relevant changes in fresh frozen plasma [18]. A reduced hematopoietic regenerative capacity in aged donors should be recognized by the regular determination of the donor's hemoglobin value before each donation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not known whether this has implications for patient outcomes. A study of the quality of fresh frozen plasma also concluded that there were no concerns about older donors contributing to the production of therapeutic or fractionated plasma . Meanwhile, Bontekoe and colleagues conducted a study of platelet quality in a small sample of donors and concluded that while there was poorer in vitro quality in platelets from older donors, this was unlikely to impact blood bank practice, and clinical implications are not known.…”
mentioning
confidence: 99%